On Recognition of Contract Asset and Contract Liability in the Financial Statements (Global Journal of Management and Business Research, 2024)
With the publication of the International Financial Reporting Standard IFRS 15 Revenue from Contracts with Customers approaches to recognition and methods of measurement of the revenues have changed fundamentally The standard considers a contract liability as a reference point for accounting coordinates for transferring control over an asset goods or services and determining the moment of recognition of revenue to the seller In the fulfillment of the performance obligations in the contract with the customer assets or liabilities may arise that are directly related to the performance of the terms of the contract by any of the parties to the contract Depending on the situation in terms of the fulfillment of the obligation by the entity and payment by the customer the entity must reflect this contract in the statement of financial condition in the form of a contract asset or a contract liability
Keywords: contracts; financial reporting; revenue from contracts with customers; contract asset; contract liability